The population of the United States since the year 1960 can be approximated by f ( t ) = 0.009 t 2 + 2.10 t + 182 where f ( t ) is the population in millions and t represents the number of years since 1960. a. Find the average rate of change in U.S. population between 1960 and 1970. Round to 1 decimal place. b. Find the average rate of change in U.D. population between 1960 and 1970. Round to 1 decimal place. c. Based on the answers from parts (a) and (b), does it appear that the rate at which U.S. population increases is increasing or decreasing with time?
The population of the United States since the year 1960 can be approximated by f ( t ) = 0.009 t 2 + 2.10 t + 182 where f ( t ) is the population in millions and t represents the number of years since 1960. a. Find the average rate of change in U.S. population between 1960 and 1970. Round to 1 decimal place. b. Find the average rate of change in U.D. population between 1960 and 1970. Round to 1 decimal place. c. Based on the answers from parts (a) and (b), does it appear that the rate at which U.S. population increases is increasing or decreasing with time?
Solution Summary: The author explains how the average rate of change in U.S. population between 1960 and 1970 is 2.2 million per year.
The population of the United States since the year 1960 can be approximated by
f
(
t
)
=
0.009
t
2
+
2.10
t
+
182
where f(t) is the population in millions and t represents the number of years since 1960. a. Find the average rate of change in U.S. population between 1960 and 1970. Round to 1 decimal place. b. Find the average rate of change in U.D. population between 1960 and 1970. Round to 1 decimal place. c. Based on the answers from parts (a) and (b), does it appear that the rate at which U.S. population increases is increasing or decreasing with time?
Solve the system of equation for y using Cramer's rule. Hint: The
determinant of the coefficient matrix is -23.
-
5x + y − z = −7
2x-y-2z = 6
3x+2z-7
eric
pez
Xte
in
z=
Therefore, we have
(x, y, z)=(3.0000,
83.6.1 Exercise
Gauss-Seidel iteration with
Start with (x, y, z) = (0, 0, 0). Use the convergent Jacobi i
Tol=10 to solve the following systems:
1.
5x-y+z = 10
2x-8y-z=11
-x+y+4z=3
iteration (x
Assi 2
Assi 3.
4.
x-5y-z=-8
4x-y- z=13
2x - y-6z=-2
4x y + z = 7
4x-8y + z = -21
-2x+ y +5z = 15
4x + y - z=13
2x - y-6z=-2
x-5y- z=-8
realme Shot on realme C30
2025.01.31 22:35
f
Use Pascal's triangle to expand the binomial
(6m+2)^2
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, algebra and related others by exploring similar questions and additional content below.
Linear Equation | Solving Linear Equations | What is Linear Equation in one variable ?; Author: Najam Academy;https://www.youtube.com/watch?v=tHm3X_Ta_iE;License: Standard YouTube License, CC-BY